Application of a Meshed Skin Graft in the Surgical Bed Immediately after Resection of Neurofibrosarcoma in the Distal Limb Region of a Dog - Cézar Nerone, Matheus; Casarin Costa, Rodrigo; Alvarez Gómez, Jorge Luiz; Del Lama Rocha, Fabiana; Camplesi, Annelise Carla; Barboza de Nardi, Andrigo (Acta Scientiae Veterinariae, 2020)
Background: Malignant peripheral nerve sheath tumors are neurogenic neoplasms that originate from cells that surround the axons of peripheral nerves. Surgery is the treatment of choice for peripheral nerve sheath tumors. They have a better prognosis when the lesion is in the extremity of a limb and the surgeon leaves wide peripheral margins after resection. However, this procedure makes local treatment a challenge due to difficult wound healing in this region. This report describes a successful case involving the use of a meshed skin graft immediately after resection of a neurofibrosarcoma in the distal region of the radius bone of a dog. Case: A 6-year-old Boxer bitch weighing 40 kg was admitted with a history of a round, firm, non-ulcerated skin nodule attached to the lateral side of the distal region of the right radius bone, which had been present for about 40 days. Fine needle aspiration cytology of the lesion showed the presence of mesenchymal cells, suggesting a sarcoma. Thus, the decision was made for an incisional biopsy to confirm the diagnosis and for the preparation of a subdermal pattern tubular flap for subsequent rotation and transposition to close the wound that would be formed after the complete removal of the lesion. After the 7th postoperative day, the diagnosis of low-grade neurofibrosarcoma was confirmed and due to the presence of necrotic onset in the middle portion of the tubular flap, further surgical intervention was scheduled for the resection of the tube flap, en bloc removal of the neoplastic lesion with peripheral margins of 2 cm, and wound closure with a free skin graft. A mesh skin graft was made with a portion of the right flank skin. The mesh graft was carefully implanted on the recipient bed using simple interrupted sutures with a 3-0 non-absorbable monofilament suture material. A dressing made with water-based sterile lubricating solution and gauze and a modified Robert Jones bandage were applied. The patient was treated with analgesic medication, antimicrobial therapy, and gastric protectors. The first bandage and dressing were changed after 48 h, and only warm physiological solution was used. Histopathological analysis confirmed the diagnosis of low-grade neurofibrosarcoma with free surgical margins. The dressing was changed every 72 h for up to 12 postoperative days, when the immobilization was removed, and wound cleaning could be completed at home using physiological solution and a dressing with nitrofurazone ointment. Granulation tissue was first seen at day 12, and at day 30 the wound was completely closed. Discussion: The primary closure of skin defects after the resection of tumors located in the distal portion of limbs is often not possible due to a lack of adjacent skin. Thus, grafts are commonly used to repair the skin in these areas using the technique presented in this report. In order to survive, skin grafts need a vascular bed capable of allowing new blood vessel connections with the implanted skin portion. There is no consensus in the literature on the best bed for graft implantations. In the case described in this study, a free mesh graft was implanted on a fresh wound without granulation tissue, which resulted in excellent clinical evolution and total survival of the graft. Excellent clinical results were achieved with the graft, since its survival and adherence to the recipient bed occurred without complications. The clinical result of this case suggests that the application of full-thickness mesh grafts to fresh wounds in distal limbs immediately after tumor resection is a good alternative when the surgical wound is too large (which prevents primary closure). Good preoperative planning associated with good surgical techniques and adequate postoperative management are essential for the success of the technique under these conditions.